2012
DOI: 10.1038/npp.2012.23
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Theta Cordance Predicts 6-Month Antidepressant Response to Subcallosal Cingulate Deep Brain Stimulation for Treatment-Resistant Depression: A Pilot Study

Abstract: Deep brain stimulation (DBS) of subcallosal cingulate white matter (SCC) may be an effective approach for treatment-resistant depression (TRD) that otherwise fails to respond to more conventional therapies, but DBS is invasive, costly, and has potential for adverse effects. Therefore, it is important to identify potential biomarkers for predicting antidepressant response before intervention. Resting-state EEG was recorded from 12 TRD patients at pre-treatment baseline, after 4 weeks SCC DBS, and after 24 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 37 publications
0
82
0
1
Order By: Relevance
“…Several groups have been working to use these local field potentials to develop biomarkers of efficacy such that a closed loop system can be developed. The use of the β band for PD (43), the θ band for depression in thesubcallosal cingulate (44), and the γ band for TS (45) in the centromedian nucleus of the thalamus (CM) may prove to be useful. Several groups are currently using a closed-loop device to record and then stimulate on demand (46).…”
Section: Figurementioning
confidence: 99%
“…Several groups have been working to use these local field potentials to develop biomarkers of efficacy such that a closed loop system can be developed. The use of the β band for PD (43), the θ band for depression in thesubcallosal cingulate (44), and the γ band for TS (45) in the centromedian nucleus of the thalamus (CM) may prove to be useful. Several groups are currently using a closed-loop device to record and then stimulate on demand (46).…”
Section: Figurementioning
confidence: 99%
“…Antidepressant effects with chronic DBS of the subcallosal ACC have been reported across a number of studies [35]; however, there is variability in patient response to this treatment and its invasive nature highlights the particular importance of identifying biomarkers which can be used to refine the use of DBS. A recent study by Broadway et al [36] investigated pretreatment and early treatment EEG markers of response in 12 patients undergoing DBS for depression. Six were classified as responders after 24 weeks of DBS and six were non-responders.…”
Section: Novel Candidate Antidepressant Treatmentsmentioning
confidence: 99%
“…Furthermore, y power has been shown to be a predictor of response to antidepressent medications in resistant depressive disorder (Bares et al, 2008) and combined y and a frontal asymmetry was shown to be a predictor of suicidal ideation during SSRI treatment (Iosifescu et al, 2008). A recent EEG pilot study pointed to frontal y cordance (FTC) at baseline (and higher FTC after 4 weeks) as a response predictor of lower depression severity scores after 24 weeks of stimulation of the SCG (Broadway et al, 2012). Several EEG studies have attempted to correlate asymmetries in resting-state parietal a to depression and anxiety symptoms (Nitschke et al, 1999;Stewart et al, 2011) generally showing an inverted hemispheric relationship between parietal a oscillations and cortical activity (Knyazev, 2007;Thibodeau et al, 2006).…”
Section: Introductionmentioning
confidence: 99%